Pengaruh Likuiditas dan Solvabilitas terhadap Nilai Perusahaan Consumer Non-Cyclicals di BEI Tahun 2020-2024 - Tanaya Cautsar Alif; Agus Taufik Hidayat (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to examine the effects of liquidity and solvency on firm value in manufacturing companies within the consumer non-cyclicals subsector listed on the Indonesia Stock Exchange during the 2020–2024 period. The study is motivated by inconsistent findings in previous research regarding the relationship between these financial indicators and firm value, particularly in the context of economic recovery, where companies are required to maintain financial stability while strengthening investor confidence. A quantitative research approach was employed using secondary data obtained from the companies' annual financial statements. The sample consisted of 24 manufacturing companies selected through purposive sampling, resulting in 120 firm-year observations. The data were analyzed using multiple linear regression after all classical assumption tests had been satisfied. The findings reveal that liquidity, measured by the Current Ratio (CR), has a positive and statistically significant effect on firm value, with a regression coefficient of 0.995 and a significance level below 0.05. Likewise, solvency, measured by the Debt-to-Equity Ratio (DER), also demonstrates a positive and statistically significant effect on firm value, with a regression coefficient of 0.672 and a significance level below 0.05. The coefficient of determination (R²) of 81.5% indicates that a substantial proportion of the variation in firm value can be explained by liquidity and solvency, while the remaining 18.5% is attributable to other factors outside the research model. The novelty of this study lies in its specific focus on manufacturing companies in the consumer non-cyclicals subsector during the 2020–2024 period, reflecting the dynamics of economic recovery and the characteristics of an industry with relatively stable demand. This study contributes to the literature by providing additional empirical evidence supporting the relevance of signaling theory in explaining the relationship between liquidity, solvency, and firm value, while offering deeper insights into the financial behavior of firms operating in Indonesia's consumer non-cyclicals subsector. From a practical perspective, the findings provide useful guidance for corporate management in formulating effective working capital and capital structure policies to enhance firm value, as well as valuable information for investors in assessing corporate fundamentals before making investment decisions. Furthermore, the findings are expected to serve as a reference for future studies investigating the determinants of firm value across different industries by incorporating additional variables and broader analytical approaches.